The jungle book - Kipling, Rudyard, 1865-1936. (New York : Oxford University Press, 2007)
Rudyard Kipling's classic children's story about the adventures of Mowgli, a young boy raised by animals in the jungles of India.
5.3
5-8
Keywords: Animals -- Juvenile fiction; Jungles -- Juvenile fiction; Mowgli (Fictitious character) -- Juvenile fiction; Animals -- Fiction; Jungles -- Fiction; Mowgli (Fictitious character) -- Fiction; Animals -- Fiction; Jungles -- Fiction; Mowgli (Fictional character) -- Fiction; India -- Juvenile fiction; India -- Fiction; India -- Fiction